383-P: Comparative Study of Serum Testosterone Levels in Male T2DM and Nondiabetic Subjects as a Risk Marker for Atherosclerotic Coronary Artery Disease - DAS, AMIT K.; BHAGAT, ABHINAV; SINHA, NEERAJ (Diabetes (New York, N.Y.), 2021)
Background: Historically, higher levels of serum testosterone were presumed deleterious to the cardiovascular system. cardiovascular disease (CVD) risk factors prevalence were increased due to low testosterone levels. Material and Methods: This was a prospective observational study, conducted among men with type 2 diabetes with documented CAD (n = 60) and controls healthy men (n = 50). Pearson correlation between sex hormones and CAD risk factors was done. The association between sex hormones and CAD risk factors among patients was analyzed by multiple logistic regression. The statistical significance was set at the 0.05 level. Result: Mean age of diabetics was 44.5 ±7.9 years and non diabetics was 42.54 ± 5.63 years. 56% of Diabetics and 20 % non diabetics had lower levels of total testosterone. 68% of Diabetics and 26 % non diabetics had lower levels of free testosterone. Mean SHBG levels in Diabetics and non - diabetics was 8.6 ± 1.8 and 16 ± 3.2. Prevalence of Hypogonadism was 22% in Diabetics and 10% in Non diabetics. Among the cases, a significant positive correlation was found between total testosterone/FTI and waist circumference, W/H ratio, triglyceride levels, hs-CRP, and CIMT (P < 0.01). In addition, a significant negative correlation was found between total testosterone and FTI with high-density lipoprotein-cholesterol levels (P < 0.01). The multiple logistic regression analysis showed that total testosterone levels (P < 0.01) and SHBG (P < 0.01) are independently associated with the occurrence of atherosclerotic CAD in T2DM men. Conclusion: We conclude that increased serum testosterone levels and low SHBG in T2DM men are associated with the development of atherosclerotic cardiovascular risk factors.